SnO2 nanorod arrays : low temperature growth, surface modification and field emission properties - Huang, Hui (2013)
SnO2 nanorod arrays have been deposited on 4 inch SiO2/Si and Si wafers and stainless steel substrates by plasma-enhanced chemical vapor deposition without any high temperature treatment or additional catalysis. The SnO2 nanorods grow up from seed nanocrystals along the [110] preferential direction by a self-catalyzed vapor–solid growth mechanism. The surface of the SnO2 nanorods was modified by ZnO, Pt and Ni nanocrystals. After surface modification, the field emission properties of the SnO2 nanorod arrays are improved. The Ni nanocrystal with sharp tips and edges act as additional field emission sites to SnO2 nanorods and thus the Ni/SnO2/SiO2/Si outperforms other samples due to the synergistic effects of good conductivity and hierarchical sharp apexes. The field enhancement factor of the Ni/SnO2/SiO2/Si increased around 3 times while the turn-on field of 8.0 V μm−1 is about one third of the SnO2/SiO2/Si device.